2001
DOI: 10.1016/s0002-9440(10)64050-3
|View full text |Cite
|
Sign up to set email alerts
|

A Putative Role for Cathepsin K in Degradation of AA and AL Amyloidosis

Abstract: The aims of this study were to investigate the role of cathepsin K in the pathology of amyloidosis by demonstrating its presence in multinucleated giant cells (MGCs) adjacent to amyloid deposits, and determining its ability to degrade amyloid fibril proteins in vitro. The study was performed using autopsy and biopsy specimens from patients with AA or AL amyloidosis. In six (55%) patients with AA amyloidosis and seven (58%) patients with AL amyloidosis, variable numbers of CD68-immunoreactive MGCs were found ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
3

Year Published

2002
2002
2010
2010

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 42 publications
3
44
0
3
Order By: Relevance
“…Augmented CatK proteolysis in atherosclerosis further links CatK to adverse vascular remodeling. Additional applications of the CatK-activatable imaging agent could include disorders of bone remodeling, 31,32 Gaucher's disease, 33 amyloidosis, 34 thyroid function, 35 prostate cancer, 36 and lung fibrosis. 37 Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…Augmented CatK proteolysis in atherosclerosis further links CatK to adverse vascular remodeling. Additional applications of the CatK-activatable imaging agent could include disorders of bone remodeling, 31,32 Gaucher's disease, 33 amyloidosis, 34 thyroid function, 35 prostate cancer, 36 and lung fibrosis. 37 Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…Auto -PBSCT treatment is capable of promptly suppressing production of M -protein and organ deposition of amyloid fibril proteins, but the elimination of the amyloid fibril proteins that have already been deposited in organs is required for the improvement of organ damage seen in the present patient. Amyloid fibril proteins deposited in tissue are surrounded by multi -nucleated giant cells, and cathepsin K, found within these cells, is known to degrade amyloid fibril proteins 17) . In addition to cathepsin K, the macrophage -derived cysteine proteases cathepsin B and cathepsin L have also been reported as degrading amyloid fibril proteins 18) .…”
Section: Discussionmentioning
confidence: 99%
“…Cathepsins C and S have been found to have the highest pH stability [54,88], while cathepsins K and V display intermediate pH stability [27,55]. In vitro investigations have shown that cathepsin K can degrade fibril proteins at neutral pH [93].…”
Section: Cysteine Proteases In Matrix Remodelling Of the Lungmentioning
confidence: 99%
“…Similar mechanisms may be involved in matrix remodelling by lung macrophages and may also contribute to the pathogenesis of granulomatous lung diseases, which are characterised by the appearance of multinucleated giant cells (MGC). Recently it was shown that MGC express and release large amounts of cathepsin K [29,93,95]. Conversely, it was shown that MGC can enclose foreign materials, micro-organisms or other extracellular components.…”
Section: Cysteine Proteases In Matrix Remodelling Of the Lungmentioning
confidence: 99%